Nasal lavage fluid sIgE levels in differential diagnostics of allergic rhinitis - Krzych-Fałta, Edyta; Lishchuk-Yakymovych, Khrystyna; Majsiak, Emilia; Borkowska, Weronika; Białek, Sławomir; Wojas, Oksana (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Differential diagnosis plays a key role in diagnosing specific types of allergic rhinitis. The method involving allergen-specific immunoglobulin E (sIgE) detection in nasal lavage fluid, which has continually been the object of standardization efforts, is characterized by high specificity/sensitivity and plays a special role in diagnosing local allergic rhinitis. This article is a systematic review of the literature on the methodology, standardization, and use of sIgE detection in nasal lavage fluid in patients undergoing diagnostic tests for allergic rhinitis.